A CROSS- SECTIONAL STUDY OF HIGHLY SENSITIVE C-REACTIVE PROTEIN IN TYPE 2 DIABETES MELLITUS AND PREDICTION OF CARDIOVASCULAR RISK WITH GLYCEMIC STATUS. - Kumar, Rakesh; Prasad, Priyanka; Sinha, Rajiv Ranjan (Student's Journal of Health Research Africa, 2024)
Background High-sensitivity C-Reactive Protein (hs-CRP) measurement may be useful for the assessment of the risk of complications in diabetes patients. So, the present study is conducted to measure plasma hs- CRP levels in type 2 diabetes mellitus (T2DM) and to determine whether adequate glycaemic control reduces hs-CRP levels. Aims and objectives The objectives of this study were to correlate HbA1c and hs-CRP in T2DM and predict cardiovascular risk with glycaemic status. Methods The authors took 50 diabetic patients. The investigation includes Fasting Blood Sugar, Postprandial Blood Sugar, hs- CRP, and Hemoglobin A1c (HbA1c). hs-CRP is measured by the immunoturbidimetry method. The reports were collected and compared with the normal reference range. Results The correlation between hs-CRP levels and HbA1c level after six months (<0.001) shows a significant relationship where mean HbA1c values on day 1 and after 6 months were 8.088±1.219 and 7.518±0.693 respectively. The hs-CRP values were 2.508±1.050 on day 1 and 2.15±0.927 after 6 months proving that better glycaemic controls decrease hs-CRP thereby decreasing cardiovascular risk. Conclusions hs-CRP values are directly related to HbA1c and better glycaemic control reduces the risk of cardiovascular disease. Recommendations The study recommends prioritizing effective glycemic control in Type 2 Diabetes Mellitus patients to lower High-Sensitivity C-Reactive Protein (hs-CRP) levels and reduce cardiovascular risk. It suggests regular monitoring of HbA1c and hs-CRP and further research to include additional factors like BMI and lipid profiles to better understand their impact on hs-CRP levels.